Rekayasa Penataan Lingkungan Permukiman Desa Mbarung - Harja, Jetno (Civiliza Publishing, 2024)
This community service project examines the settlement environmental planning in Desa Mbarung, Kecamatan Babussalam, Kabupaten Aceh Tenggara, Aceh Province. The focus of this study is to prioritize settlement environmental planning using the ArcGIS program, aiming to identify which development areas and types should be prioritized. Data analysis was conducted through direct field observation surveys and processed using Microsoft Excel before being entered into ArcGIS for visualization and prioritization. The survey covered various aspects, including geographical location, population density, housing conditions, accessibility, drainage, drinking water services, and wastewater disposal systems. The study results reveal the characteristics and criteria for each parameter of settlement environmental planning, as well as the necessary development priorities. Key findings include the percentage of residential buildings lacking adequate roofing, flooring, and walls according to technical standards; the percentage of roads not meeting technical requirements; the percentage of drainage networks in settlements having substandard quality; the percentage of the population lacking access to adequate drinking water facilities (both piped and protected non-piped sources); and the percentage of households without access to family or communal latrines (with five households per latrine).